Relationship between the parameters describing the feet position and the performance of elite seated discus throwers in Class F33/34 participating in the 2002 IPC World Championships - O'Riordan, A.; Goodman, S.; Frossard, L. A. (AAESS Exercise and Sports Science Conference, 2003)
A total of 59 attempts were filmed, which included all 6 throwing trials for all discus competitors placed in the top 6, and the majority for those finishing in places 7-12. Video footage was collected using 50 Hz video data recorded with a camera situated behind the athlete. The approximate instant of release of the discus was identified. The position of the feet at this instant was then tracked using Digitiser 5.0.3.0 software (SiliconCOACH Ltd). Calibration was possible by utilising the measurement dimensions of the throwing plate (a steel rectangle plate that is secured to the ground by which the athletes` throwing frames are attached), and the maximum height of the throwing frames, as stipulated by the International Paralympic Committee. Other points tracked were the corners of the throwing plate and the top and bottom points of the athletes` throwing frames. All points were tracked in relation to the origin of the Global Coordinate System located on the floor in front of the throwing frame. Results showed that there was no definite link between feet position and performance. The data did confirm however, that feet position is related to each athlete`s functional level and physical ability, and that each athlete`s technique as a result, is unique and individual. Results also showed that if a throwing frame is to be designed that caters for all athletes` functional levels, then it needs to be extremely adjustable. It is anticipated that the results of this study will provide key information to those facing the challenge of improving the understanding of the interaction between throwing technique of elite seated throwers and their throwing frame.